## Trending News

# Solve x2 + 7x + 6 = 0 for x?

Solve x2 + 7x + 6 = 0 for x

### 19 Answers

- SAMUEL DLv 71 decade agoFavorite Answer
x² + 7x + 6 = 0

(x + 6) (x + 1)

- - - - - - - - -

Roots

x + 6 = 0

x + 6 - 6 = 0 - 6

x = - 6

- - - - -

x + 1 = 0

x + 1 - 1 = 0 - 1

x = - 1

- - - - - - -

x = - 6

or

x = - 1

- - - - - - - -s-

- Login to reply the answers

- PhiloLv 71 decade ago
x² + 7x + 6 = 0

x² + 7x = -6

x² + 7x + (7/2)² = -6 + (7/2)²

(x + 7/2)² = -24/4 + 49/4

(x + 7/2)² = 25/4

x + 7/2 = ± 5/2

x = -7/2 + 5/2 or x = -7/2 - 5/2

x = -2/2 or x = -12/2

x = -1 or x = -6

that's completing the square, which always works, but factoring, when it works, is easier.

x² + 7x + 6 = 0

(x + 6)(x + 1) = 0

x + 6 = 0 or x + 1 = 0

x = -6 or x = -1

- Login to reply the answers

- 1 decade ago
x^2 + 7x + 6 = 0

(x + 1)(x + 6) = 0

(x + 1) = 0 or (x + 6) = 0

x = -1 x = -6

- Login to reply the answers

- 1 decade ago
just sustitute

0 x 2 + 7 x 0 + 6 = 20

multiply 2 and 7 by 0 then add the products then add 6!

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- 1 decade ago
I assume X2 means X^2 and it is a quadratic equation.

factor or use the quadratic formula

I chose to factor as it factors easily w/o doing a lot of algebra

(X+1)(X+6)=0 therefore:

X= -1

and X= -6

- Login to reply the answers

- Sherman81Lv 61 decade ago
x^2 + 7x + 6 = 0

(x + 1)(x + 6) = 0

x = -1 or -6

If you aren't certain of an answer, you can always do this.

x = (-b ± sqrt(b^2 - 4ac))/(2a)

x = (-7 ± sqrt(7^2 - 4(1)(6)))/(2(1))

x = (-7 ± sqrt(49 - 24))/2

x = (-7 ± sqrt(25))/2

x = (-7 ± 5)/2

x = (-12/2) or (-2/2)

x = -6 or -1

- Login to reply the answers

- yupchageeLv 71 decade ago
x^2 + 7x + 6 = 0

(x+6)(x+1)=0

x+6=0

x=-6

x+1=0

x=-1

x=-6, -1

- Login to reply the answers

- Anonymous1 decade ago
x ^2+7x+6

=x^2+x+6x+6

=x(x+1)+6(x+1)

=(x+1)(x+6)

i.e,x=-1 or x=-6

- Login to reply the answers

- ignoramusLv 71 decade ago
(x+1) (x+6) =0

divide first by x +6

x+1 = 0

x = -1

next divide top equation by x +1

then, x+6 =0

x= -6

- Login to reply the answers